2004
DOI: 10.1111/j.1365-2443.2004.00786.x
|View full text |Cite
|
Sign up to set email alerts
|

The transactivating function of peroxisome proliferator‐activated receptor γ is negatively regulated by SUMO conjugation in the amino‐terminal domain

Abstract: Peroxisome proliferator-activated receptor (PPAR)-γ γ γ γ 2, a member of the nuclear hormone receptor superfamily, plays a key role in adipocyte differentiation. Its amino-terminal region carries a ligandindependent gene-activating function, AF-1, and is composed of activation as well as repression domains. We have found PPARγ γ γ γ 2 and its isoform, PPARγ γ γ γ 1, to be modified by small ubiquitin-related modifier (SUMO)-1 in vivo , at a lysine residue in the repression domain. In reporter assays, a sumoylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
132
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(141 citation statements)
references
References 42 publications
8
132
0
1
Order By: Relevance
“…PPAR also undergoes sumoylation at lysine 107 in the AF1 and lysine 395 A c c e p t e d M a n u s c r i p t 8 in the AF2 region [37]. Sumoylation of the AF1 domain represses PPAR transcriptional activity and accordingly a sumoylation-defective PPAR 2 mutant (bearing a lysine 107 to arginine substitution) promoted adipogenesis more efficiently than wild-type PPAR 2 when ectopically expressed in NIH-3T3 cells [38][39][40]. In contrast, lysine 395 sumoylation is not involved in the regulation of direct PPAR target genes but rather in the transrepression of inflammatory genes by PPAR in macrophages [41].…”
Section: Page 7 Of 25mentioning
confidence: 99%
“…PPAR also undergoes sumoylation at lysine 107 in the AF1 and lysine 395 A c c e p t e d M a n u s c r i p t 8 in the AF2 region [37]. Sumoylation of the AF1 domain represses PPAR transcriptional activity and accordingly a sumoylation-defective PPAR 2 mutant (bearing a lysine 107 to arginine substitution) promoted adipogenesis more efficiently than wild-type PPAR 2 when ectopically expressed in NIH-3T3 cells [38][39][40]. In contrast, lysine 395 sumoylation is not involved in the regulation of direct PPAR target genes but rather in the transrepression of inflammatory genes by PPAR in macrophages [41].…”
Section: Page 7 Of 25mentioning
confidence: 99%
“…Small ubiquitinlike modifier (SUMO), a protein structurally homologous to ubiquitin, is another important regulator of PPARg. SUMOylation can occur in the AF-1 domain at Lys-107 of PPARg2 or Lys-77 of PPARg1 to control stability and activity (Floyd and Stephens 2004;Ohshima et al 2004;Yamashita et al 2004;Pascual et al 2005). PPARg can also be SUMOylated in a ligand-dependent manner in the LBD at Lys-365 (Pascual et al 2005).…”
Section: Ppargmentioning
confidence: 99%
“…Several studies have revealed that a range of substances produced by induction of asthma, such as 15-hydroxyeicosateraenoic acid or IL-4, can activate PPAR␥ and enhance its expression (13, 29 -32). In addition, PPAR␥2 used in this study possesses ligand-dependent and considerable ligand-independent transactivation potential (33)(34)(35). Therefore, we suggest that the stimulation for AdPPAR␥ by the increased several substances and cytokines produced in the airways of asthmatics and the ligand-independent activation of PPAR␥2 could be possible mechanisms for the constitutive PPAR␥ activation by AdPPAR␥ without ligands in our present asthmatic lungs.…”
Section: Discussionmentioning
confidence: 80%